Use of vitamin D supplements during infancy in an international feeding trial. Issue 4 (24th June 2013) - Lehtonen, Eveliina; Ormisson, Anne; Nucci, Anita; Cuthbertson, David; Sorkio, Susa; Hyytinen, Mila; Alahuhta, Kirsi; Berseth, Carol; Salonen, Marja; Taback, Shayne; Franciscus, Margaret; González-Frutos, Teba; et al.
Abstract Objective To examine the use of vitamin D supplements during infancy among the participants in an international infant feeding trial. Design Longitudinal study. Setting Information about vitamin D supplementation was collected through a validated FFQ at the age of 2 weeks and monthly between the ages of 1 month and 6 months. Subjects Infants (n 2159) with a biological family member affected by type 1 diabetes and with increased human leucocyte antigen-conferred susceptibility to type 1 diabetes from twelve European countries, the USA, Canada and Australia. Results Daily use of vitamin D supplements was common during the first 6 months of life in Northern and Central Europe (>80 % of the infants), with somewhat lower rates observed in Southern Europe (>60 %). In Canada, vitamin D supplementation was more common among exclusively breast-fed than other infants (e.g. 71 % v. 44 % at 6 months of age). Less than 2 % of infants in the USA and Australia received any vitamin D supplementation. Higher gestational age, older maternal age and longer maternal education were study-wide associated with greater use of vitamin D supplements. Conclusions Most of the infants received vitamin D supplements during the first 6 months of life in the European countries, whereas in Canada only half and in the USA and Australia very few were given supplementation.